SPASIAL DAN PERENCANAAN PENYAKIT ISPA PADA ANAK UMUR DIBAWAH 5 TAHUN DI KABUPATEN KONAWE, SULAWESI TENGGARA - Ramadhan Tosepu; Nelson Sula; Hasbullah Syaf (Universitas Halu Oleo, 2019)
ARI is one of the public health problems that until now has not been handled properly. Indonesia as a tropical country makes ISPA a disease that often occurs in the community. This study aims to analyze the spatial and planning of acute respiratory infections in children under 5 years in Konawe District, Southeast Sulawesi Province. The method used in the form of spatial analysis of ARI is found that patients with ARI are higher in the female group. As well as the peak event occurred in July. Also found the distribution of acute respiratory infections in Konawe district, there are eight districts in the high category, consist of: Abuki, Uepai, Lambuya, Meluhu, Wawotobi, Konawe, Amonggedo, and Soropia.Keywords: Acute respiratory infections, Konawe, Indonesia